Canada-Denmark MRI scoring system of the spine in patients with axial spondyloarthritis: updated definitions, scoring rules and inter-reader reliability in a multiple reader setting. Issue 2 (13th October 2019) - Krabbe, Simon; Østergaard, Mikkel; Pedersen, Susanne J; Weber, Ulrich; Kröber, Georg; Makysmowych, Walter; Lambert, Robert G W
Abstract : Objective: To validate the Canada-Denmark (CANDEN) MRI scoring system for the spine in axial spondyloarthritis with updated lesion definitions. Methods: Lesion definitions in the CANDEN system were updated and illustrated by a consensus set of reference images. Sagittal spine MRIs of 40 patients with axial spondyloarthritis obtained at baseline and at week 52 after initiation of treatment with the tumour necrosis factor inhibitor golimumab were evaluated in unknown chronology by seven readers blinded to all other data. Results: CANDEN MRI spine inflammation score had very good reliability for status scores (single-measure intraclass correlation coefficient (ICC) of 21 reader pairs median of 0.91 (IQR 0.88–0.92)) and change scores (ICC 0.88 (0.86–0.92)). CANDEN MRI spine fat score had good to very good reliability for status scores (ICC 0.79 (0.75–0.86)) and moderate to good reliability for detecting change (ICC 0.59 (0.46–0.73)). CANDEN MRI spine bone erosion score and CANDEN MRI spine new bone formation score had slight to moderate reliability for status scores (ICC 0.38 (0.32–0.52) and 0.39 (0.27–0.49), respectively). Conclusion: The CANDEN MRI spine scoring system allows a comprehensive evaluation of inflammation, fat, bone erosion and new bone formation of the spine in patients with axial spondyloarthritis. It demonstrated very good reliability for detecting change in inflammation, moderate to good reliability for detecting change in fat, and slight to moderate reliability for detecting bone erosions and new bone formation. Studies with longer follow-up or patients with more advanced spinal involvement may be needed to reliably detect change in bone erosion and new bone formation scores. Trial registration number: NCT02011386 .